Prognostic Factors Associated with Disability in a Cohort of Neuromyelitis Optica Spectrum Disorder and MOG-Associated Disease from a Nationwide Portuguese Registry. - Moura, João (2024)
Introduction: Neuromyelitis optica spectrum disorders (NMOSD) and MOG-associated disease (MOGAD) are an increasingly recognized group of demyelinating disorders of the central nervous system. Previous studies suggest that prognosis is predicted by older age at onset, number of relapses, the severity of the first attack and autoantibody status. Objective: To study prognostic factors associated with disability progression and additional relapses in the 3-year follow-up of a national NMOSD/MOGAD cohort. Results: Out of 180 of the initial Portuguese cohort, data on 82 patients was available at the end of the follow-up period (2019-2022). Two patients died. Twenty (24.4%) patients had one or more attack in this period (25 attacks in total), mostly transverse myelitis (TM) (56.0%) or optic neuritis (32.0%). MOGAD was significantly associated with a monophasic disease course (p = 0.03), with milder attacks (p = 0.01), while AQP4 + NMOSD was associated with relapses (p = 0.03). The most common treatment modalities were azathioprine (38.8%) and rituximab (18.8%). AQP4 + NMOSD more frequently required chronic immunosuppressive treatment, particularly rituximab (p = 0.01). Eighteen (22.5%) had an EDSS ≥6 at the end of the follow-up. AQP4 + NMOSD (p < 0.01) and the occurrence of transverse myelitis (TM) during disease (p = 0.04) correlated with an EDSS≥6 at the end of the follow-up period. MOGAD was significantly associated with an EDSS<6 (p < 0.01), and MOG+ cases that reached an EDSS>6 were significantly older (64.0 ± 2.8 versus 31.0 ± 17.1, p = 0.017). A bivariate logistic regression model including the serostatus and TM attacks during disease history successfully predicted 72.2% of patients that progressed to an EDSS≥6. Conclusion: This study highlights that myelitis predict increased disability (EDSS≥6) in NMOSD/MOGAG and AQP4 positivity is associated with increased disability.